OPTN/SRTR 2020 Annual Data Report: Living Donor. (10th March 2022) - Kasiske, B. L.; Lentine, K. L.; Ahn, Y.; Skeans, M. A.; Eberhard, T.; Folken, C.; Wainright, J.; Larkin, L.; Nystedt, C.
Abstract: The first successful solid organ transplant was a living donor kidney transplant in 1954. Since then, living donation has been an important source of organs for kidney and liver transplants in the United States. Unfortunately, the demand for organs has not kept pace with the supply, and unlike deceased donor transplant, there has been little growth in the number of living donor transplants over the past decade. To better understand possible barriers to living donation and long‐term risks attributable to donation, the Health Resources and Services Administration (HRSA) directed the Scientific Registry of Transplant Recipients (SRTR) to establish a national registry of all living donor candidates and donors evaluated at US transplant programs to acquire lifetime follow‐up information. Other goals include understanding the factors associated with candidate approval and variation in approval practices across centers. A pilot program was conducted from June 2018 through September 2020 to inform baseline data collection and registration processes. In September 2020, the registry began recruiting additional sites evaluating candidates for living donation. Here, we describe candidates registered at participating living donor kidney and liver programs, from June 2018 through the end of 2020. Not all programs submitted data throughout the whole period. Data for kidney and liver living donor candidates are presented separately.